Ethnic differences in socioeconomic status, diagnosis, treatment, and survival among older women with epithelial ovarian cancer. Issue 4 (1st July 2008) - Du, X. L.; Sun, C. C.; Milam, M. R.; Bodurka, D. C.; Fang, S.
Abstract : The purpose of the study was to determine the ethnic disparities in socioeconomic status (SES) and in receiving definitive surgical treatment and adjuvant chemotherapy and to examine if these differences contribute to ethnic disparities in survival. We studied a population-based cohort of 5131 women diagnosed with epithelial ovarian cancer at age ≥ 65 between 1992 and 1999, identified from the Surveillance, Epidemiology and End Results-Medicare linked databases with up to 11 years of follow-up. The percentage of women diagnosed with epithelial ovarian cancer at advanced stage (stage III or IV) was 71.6% in Caucasians and 69.7% in African-Americans. Of these 4264 with stage IC–IV disease who are recommended for chemotherapy, fewer African-Americans received chemotherapy compared to Caucasians (50.2% versus 64.7%, P < 0.001). The risk of all-cause mortality in African-Americans was not significantly different from Caucasians (hazard ratio [HR] = 1.00, 95% CI = 0.88–1.13) after controlling for patient demographics, tumor characteristics, and comorbidity. The HR remained not significant in African-Americans compared to Caucasians after additionally adjusting for treatments (0.93, 0.82–1.06) or SES (0.94, 0.82–1.08) or both (0.88, 0.77–1.01). Women who underwent cancer-directed surgery and received adjuvant chemotherapy were 50% less likely to die than those who did not. The survival benefits from these therapies were similar in Caucasian and African-American women with ovarian cancer. There was no significant difference in survival between African-American and Caucasian women with ovarian cancer after adjusting for tumor characteristics, treatment, and sociodemographic factors. Although adjuvant chemotherapy was effective in prolonging survival, substantial numbers of women with ovarian cancer still did not receive chemotherapy.